Systematic literature review on cultivating reading culture in academic library initiatives / Samsul Farid Samsuddin, Nona Zurena Masenwat and Liza Ab Llah - Samsuddin, Samsul Farid; Masenwat, Nona Zurena; Llah, Liza Ab (Universiti Teknologi MARA, 2021)
Academic library initiatives aim to promote a reading culture among higher education institution patrons to provide support in their learning and excelling in their studies. Changes in library user behavior correspond to the changes in instructional program delivery and information management to meet the academic library users' needs. Few studies have been carried out on academic library research, particularly on initiatives in cultivating reading culture. Thus, a global systematic literature review was conducted using existing literature. There were three main steps involved in this systematic review method, namely identification, screening, and eligibility process. Guided by the Realist and Meta-narrative Evidence Syntheses: Evolving Standards (RAMESES) review method, the systematic literature review identified 18 related studies throughout Dimensions, Scopus, and Web of Science databases. Five main themes were found from the analysis, namely roles, promotions, services and facilities, collections and information resources, and capabilities. Additionally, 23 sub-themes were also identified from the main themes. Based on the in-depth qualitative study on academic library efforts and initiatives in promoting reading culture among library users, the provision of suitable reading materials (leisure reading materials) and the use of readership promotion campaigns by the libraries were recommended. Selected databases used as information searching resources have generated several relevant previous pieces of indexed literature, further research is needed to include non-index literature using the same purpose to obtain a better understanding of academic libraries' initiatives in cultivating reading culture among library users.